PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN KERAJINAN â€œBU FIAâ€ (BONSAI JAMBU RAFIA) PADA PKK DESA JATIREJO - Maulana, Rizal; Wulandari, Sintya; Putra, Gilang Rochmadi; Muhtaji, Ahmad; Ismiasih, Ismiasih (Jurnal Industri Kreatif dan Kewirausahaan, 2024)
Community empowerment is one way to build human capacity and increase community participation in sustainable development. Bonsai Jambu Rafia (Bu Fia) Craft Program is an empowerment activity carried out as an effort to optimize the potential of human resources in the Pemberdayaan Kesejahteraan Keluarga (PKK) institution of Jatirejo village. The method used is training and practice with a participatory approach (Participatory Rural Appraisal). This activity provides training and knowledge about guava stem and branch waste to be processed into handicrafts with high selling value. The goal is to bring the results of innovation based on local resources of guava stem and twig waste to the community, provide solutions to the needs of village partners in improving the economy, and prepare third parties for sustainable sales. The result was increased knowledge, skills, and independence for PKK members.